Integrating Digital Marketing and Green Innovation: How Gen Z Entrepreneurial Orientation Shapes MSME Marketing Performance - Milla Permata Sunny; Made Setini; Anhar Yani (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2026)
Purpose – This study examines the effects of Digital Entrepreneurial Marketing (DEM) and Green Product Innovation (GPI) on MSME Marketing Performance (MP), investigates the interaction between digital and green capabilities, and analyzes the moderating role of Gen Z Entrepreneurial Orientation (GZEO) in strengthening this relationship. Methodology/approach – A quantitative explanatory research design was employed using data collected from 110 Gen Z entrepreneurs managing food and beverage MSMEs in Bali, Indonesia. Respondents were selected through purposive sampling, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The analysis included measurement model assessment, structural model evaluation, and bootstrapping for hypothesis testing. Findings – The results show that Digital Entrepreneurial Marketing has a positive and significant effect on MSME Marketing Performance (β = 0.284; p = 0.004), while Green Product Innovation also has a positive and significant effect (β = 0.246; p = 0.012). Moreover, the interaction between DEM and GPI significantly improves marketing performance (β = 0.221; p = 0.020). Gen Z Entrepreneurial Orientation positively moderates the effect of digital-green capability integration on marketing performance (β = 0.198; p = 0.029). The model explains 61.2% of the variance in MSME Marketing Performance (R² = 0.612), indicating substantial explanatory capability. Originality/value – This study contributes to the MSME literature by conceptualizing digital entrepreneurial marketing and green product innovation as complementary and interacting strategic capabilities rather than merely independent predictors of performance. It further identifies Gen Z entrepreneurial orientation as a boundary condition that strengthens the performance benefits generated by digital-green capability integration in Gen Z-led food and beverage MSMEs. Keywords: Digital Entrepreneurial Marketing; Green Product Innovation; Gen Z Entrepreneurial Orientation; MSME Marketing Performance; Digital-Green Capability Integration; PLS-SEM.